PERTUMBUHAN DAN DAYA HASIL BAWANG MERAH (Allium ascolanicum L.) DENGAN PEMBERIAN PUPUK KALIUM DAN PUPUK KANDANG AYAM PADA UKURAN BIBIT YANG BERBEDA - Armaini Armaini; Tri Hardianti; Irfandri Irfandri (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
Shallot productivity can be increased by taking into account the right fertilizer factor and the potential of the seeds used. The study of potassium and manure dosages and seed size were carried out to get the best treatment in increasing growth and yield. The study was conducted in the Experimental Garden of the Faculty of Agriculture, University of Riau, from February to April 2019, using a divided plot design. The main plot is the difference in seed size (> 5.0 - 7.5 and 2.5 - 5.0) g, subplots of doses of manure (0, 15, 30) ton.ha-1 and children of subplots (0 , 200, 400) kg.ha-1. The parameters observed were plant height, number of leaves, age of harvest, number of tubers per clump, diameter of tuber, tuber fresh weight and tuber dry weight, further tests used BNJ level of 5%. The results showed that the highest dry weight of tubers was obtained in the treatment of large seedlings (> 5.0 - 7.5 g) which were given 30 tons. ha-1 of manure and 400 kg.ha-1 of KCl, with an achievement of 4.1 tons.ha-1.